Clinico-microbiological profile on multidrug-resistant enterococci in urinary tract infection patients in a tertiary care hospital - Rupak Chatterjee; Aitihya Chakraborty; Malabika Biswas; Shatavisa Mukherjee; Banya Chakraborty; Nandini Chatterjee; Partha Sarathi Karmakar; S Anuradha; Netai Pramanik (Wolters Kluwer Medknow Publications, 2024)
Background: Considering enterococci as an emerging important cause of nosocomial infections, and antibiotic resistance by Enterococcus as a major obstacle for treatment, determination of the prevalence of various Enterococcus species and their antibiotic resistance pattern among urinary isolates is very crucial and need of the hour. The present study tried to identify the burden of urinary tract infections (UTIs) caused by Enterococcus species and analyze the current antibiotic susceptibility patterns of the uropathogenic isolates and evaluate the risk factors. Methods: A cross-sectional study included all clinico-microbiologically diagnosed cases of admitted UTI cases. Hospital records were analyzed for the clinical background of the UTI cases, and urine sample was collected and processed for antibiotic susceptibility testing. Data were statistically analyzed. Results: Out of the 372 urine samples, Enterococcus spp. was identified in 13.44% of isolates as the causal uropathogen. Enterococcus faecalis was the predominant species identified, followed by Enterococcus faecium. Cases were mostly observed in clinical settings of sepsis followed by pyelonephritis and cystitis. Antimicrobial susceptibility profile showed that resistance was most frequently observed with norfloxacin followed by levofloxacin, ciprofloxacin, ampicillin, and high-level gentamicin. Linezolid showed maximum sensitivity, followed by vancomycin, nitrofurantoin, and others. Conclusion: The rise of multidrug-resistant (MDR) Enterococcus species is of particular concern in terms of antibiotic therapy. Speciation along with routine culture and sensitivity is essential to gather knowledge about the available antibiotics in MDR uropathogenic Enterococcus species, particularly oral choices.